Formación de redes de Stackelberg no cooperativas - Larrosa, Juan Manuel Ceferino (2014)
Non-cooperative network formation games in industrial organizations analyze how firms create links. We assume that links portray cost-reducing information and that access to this information is not reciprocal. We study the consequences in terms of profits if one firm can move first in establishing a link. A classic model of exogenous Stackelberg leadership is developed and first-mover advantage is observed.